Artifizialität und Agon Poetologien des Wi(e)derdichtens im höfischen Roman des 12. und 13. Jahrhunderts - Stellmann, Jan (Andere Ästhetik - Studien, 2022)
This study develops the theory that the practice of retelling reflected in the poetologies of German chivalric romance (12th and 13th cent.) must be understood not just as artificial poiesis but also as a practice of imitation and dispute. It describes these two dimensions conceptually using the concepts of artificiality and agon.